Improving the finite element ordering for the frontal solver - Negre, Stephane; Boufflet, Jean Paul; Carlier, Jacques; Breitkopf, Piotr (European Journal of Computational Mechanics, 2000)
We present the structure of greedy methods used for reordering the nodes or the finite elements of a mesh and we propose two improvements that can be easily implemented in existing software. We investigate a wave reordering method which adapts the reordering strategy during the reordering process. Then, we propose an adaptation of the Tabu Search optimization technique for finite element reordering. The results show the efficiency of the improvements The wave reordering method and the Tabu Search provide very good solutions offering a motivation to carry on research for optimizing their computing time.